(untitled) (ELS Journal on Interdisciplinary Studies in Humanities, 2024)
The ideology and socio-political viewpoints of writers significantly shape text and language products. Hence, students engaging in literacy tasks, such as reading and writing, should approach them with a critical mindset, considering various perspectives rather than accepting information uncritically. Critical literacy pedagogy addresses these requirements, aiming to cultivate critical literacy skills in students with the guidance of teachers, who themselves must possess critical thinking abilities and literacy. This study explores English teachers’ perceptions and grasp of critical literacy pedagogy. Sixty teachers participated, responding to questionnaires comprising both closed and open-ended questions, alongside brief interviews. The data obtained, quantitative and qualitative, were analyzed through mathematical computations and coding techniques respectively, revealing teachers’ positive attitudes toward critical literacy pedagogy. However, this enthusiasm wasn’t consistently reflected in its implementation due to cultural beliefs and insufficient teacher knowledge. Consequently, the study recommends professional development opportunities for teachers to enhance their understanding and proficiency in incorporating critical literacy pedagogy, particularly within EFL contexts.